NATIONAL AND INTERNATIONAL SPORTS DISPUTE RESOLUTION BODIES - Biguzas, Audrius (Teisė, 2015)
The article analyses possibilities of professional sports’ subjects to resolve their disputes by using various dispute resolution bodies. The article analyses drawbacks of courts of general competence, as well as it provides for possibilities to resolve sport disputes using the method of alternative dispute resolution and arbitration.